Weibo or WeChat? Assessing Preference for Social Networking Sites and Role of Personality Traits and Psychological Factors - Hou, Juan; Ndasauka, Yamikani; Pan, Xuefei; Chen, Shuangyi; Xu, Fei; Zhang, Xiaochu (Frontiers in Psychology, 2018)
Research trying to understand individual difference in the use of different social networking sites (SNSs) is minimal. In the present study, we collected data from 714 college students in China (273 males) to assess how personality traits and psychological factors relate to excessive use of WeChat and Weibo. We found that excessive use of Weibo and WeChat correlated positively with neuroticism, loneliness, and external locus of control and negatively with agreeableness, social support and social interaction. Furthermore, people that scored high on loneliness, lack of social support and poor social interaction skills excessively used Weibo more than WeChat. These results entail that by fulfilling different needs, WeChat and Weibo attract different kinds of people; significant lesson for future development of SNSs.